Ease, Comfort, and Performance of the HerSwab Vaginal Self-Sampling Device for the Detection of Chlamydia trachomatis and Neisseria gonorrhoeae. Issue 2 (February 2016) - Arias, Manuel; Jang, Dan; Gilchrist, Jodi; Luinstra, Kathy; Li, Jenny; Smieja, Marek; Chernesky, Max A.
Abstract : Background: Many sexually transmitted diseases are asymptomatic in the lower genital tract and can cause upper tract complications if left untreated. Self-collected vaginal (SCV) swabs enable the accurate detection of many sexually transmitted infections and give women the option of collecting their own samples while providing them with privacy and convenience. Methods: We compared SCV samples collected and transported dry using the HerSwab device to physician-collected vaginal (PCV) Aptima swabs for the detection of Chlamydia trachomatis ( CT ) and Neisseria gonorrhoeae ( NG ), and measured patients' ease and comfort with self-collection. A total of 189 women aged 16 to 41 years were consented into the study and answered a standardized anonymized questionnaire regarding self-collection with the HerSwab device. Results: Women reported self-collection with HerSwab to be easy (97.1%) and comfortable (88.3%). They preferred self-collection over physician collection (80.9%) and would consider using HerSwab for self-collection at home (79.7%). Samples of SCV and PCV showed an overall agreement of 94.7% ( κ = 0.64) for CT and of 98.4% ( κ = 0.56) for NG, and HerSwab collection detected 7 more positive patients than PCV collection. The overall prevalence of infection was 10.6% for CT and 2.6% for NG . Conclusion: HerSwab SCV samples are suitable for the diagnosis of CT and NG . Abstract : In a study of 189 women, patients' found it easy and preferred HerSwab vaginal self-collection over vaginal physician collection with an Aptima swab. More Chlamydia trachomatis and Neisseria gonorrhoeae positives were detected from the HerSwab.